Contribution to knowledge of the myrmecofauna in the municipality of San Antero, Córdoba, Colombia - DIX-L., OSCAR JAVIER; MARTÍNEZ-V., JULIO CÉSAR; FERNÁNDEZ-H., CLAUDIO (Revista Colombiana de Entomología, 2005)
Field work conducted in the municipality of San Antero, department of Córdoba, Colombia, between the months of February and August of 2002, led to the identification and comparison of the diversity, composition, bioindication potential and ecological aspects of the communities of ants that live in two systems with distinct degrees of human intervention, a pasture and a secondary gallery forest. Twenty sampling stations were located at each site, and 5 types of traps were used: baits 15 cm below ground, on the soil surface and in trees, pitfall traps, and manual collection. For the comparisons between areas, we applied species richness estimators (Jacknife 1),, diversity indices (Shannon), exclusive species, number of species by subfamily, equitability, evenness, similarity and Hill numbers. Altogether 54 species grouped in 16 tribes, 32 genera and 6 subfamilies were collected. The estimator Jacknife 1 indicated that 73% of the myrmecofauna in each system was sampled. Although richness and the number of exclusive species captured were greater in the secondary forest than in the pasture, no significant differences between the diversity values were detected. The Sorenson similarity coefficient showed that the sites are not very similar in relation to their richness because of 54 collected species only 15 were common to both systems. The comparison of averages between the richness of the sites determined that the subfamilies Ponerinae and Myrmicinae have a high and medium sensitivity, respectively to increasing degree of disturbance.